KEIKUTSERTAAN KB PASCAPERSALINAN PADA IBU YANG MENGGUNAKAN JAMINAN PERSALINAN - Widiyanti, Desi (JURNAL MEDIA KESEHATAN, 2014)
Using postpartum family planning is very effective in achieving success of national family planning program. Participation in postpartum family planning program of mothers using baby delivery insurance is influenced by several factors. The study was analytic cross-sectional on 100 postpartum mothers who used jampersal at the Kepahiang District General Hospital in Bengkulu Province during the period July to September 2012. Chi square and Fisher's Exact test were used for bivariable analysis and multiple logistic regression for multivariable analysis. The results showed that there was a significant influence to probability value P<0.05 from the knowledge factor (P= 0.006), religion view (P= 0.001), access for information (P= 0.002), health care provider’s support (P= 0.004), and husband’s support (P= 0.002) for participation of postpartum family planning in women who used jampersal at hospital. Husband’s support was the dominant factor in the participation of postpartum family planning and 6.4 times likely to increase the participation of postpartum family planning.